Post-mortem Diagnosis of Management-induced Proventricular Impaction, Rickets, and Tibiotarsal Bone Rotation in a 3-month Old Ostrich (Struthio camelus) (African Journal of Biomedical Research, 2021)
Ostriches are big birds whose growth rate requires adequate nutrition and somewhat clean environments especially for captive ones. This particular ostrich and the remaining three members of the herd, which sparingly fed on green spinach (Spinacia oleracea) and occasionally, some commercial chicken grower mash, lived in an unkempt environment with no vaccination or medical history. Although there are reports of proventricular impaction, rickets, and tibiotarsal rotation separately in ostriches, their co-existence in an ostrich needs documentation to deepen the current knowledge based concerning its predisposing factors and pathophysiology of the case. A post-mortem examination of a fresh ostrich carcass revealed over-distended proventriculus with considerable amounts of foreign materials, “rachitic rosary” beads in both ribs, and comparatively swollen and angulated or rotated left tibiotarsal bone. These led to a diagnosis of chronic proventricular impaction associated with rickets and tibiotarsal deformity predisposed by poor management practice. Therefore, the prompt and adequate feeding of balanced diets in the right amount and at the right time in a cleaner environment would have prevented the development of the conditions in this captive ostrich